Severe Rigid Scoliosis: Review of Management Strategies and Role of Spinal Osteotomies - Kandwal, Pankaj (Asian Spine J, 2017)
Severe rigid curves pose a considerable challenge to the treating spine surgeon. In our practice, approximately 30%–40% of patients with scoliosis present late with severe rigid scoliosis (>90° and <30% correction on bending films). Controversy still exists with regard to the ideal surgical strategy for correcting these rigid curves. Rigid scoliosis often presents in the form of either sharp angular or rounded deformities. Rounded deformities can be effectively managed with an anterior release to loosen the apex and posterior instrumentation (with osteotomies, if required). In contrast, severe rigid scoliosis, which is a sharp angular deformity, is not very amenable to anterior release and is best managed by posterior-only vertebral column resection and posterior instrumentation.